2014
DOI: 10.1080/09593330.2014.957730
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic biodegradation of trichloroethylene and phenol co-contaminants in groundwater by a bacterial community using hydrogen peroxide as the sole oxygen source

Abstract: Trichloroethylene (TCE) and phenol were often found together as co-contaminants in the groundwater of industrial contaminated sites. An effective method to remove TCE was aerobic biodegradation by co-metabolism using phenol as growth substrates. However, the aerobic biodegradation process was easily limited by low concentration of dissolved oxygen (DO) in groundwater, and DO was improved by air blast technique with difficulty. This study enriched a bacterial community using hydrogen peroxide (H2O2) as the sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Instead, the key group was the Gammaproteobacteria, irrespective of the presence or absence of TCE. Members of Gammaproteobacterial groups such as Pseudomonas, Bacillus, Stenotrophomonas and Acinetobacter sp are associated with TCE enrichment cultures or contaminated sites [45,46]. Alongside, alpha-and betaproteobacteria groups (also detected in this study), these organisms are believed to be involved in the co-metabolism of the TCE contaminant [46].…”
Section: Microbial Community Associated With Tce Dechlorinationmentioning
confidence: 86%
“…Instead, the key group was the Gammaproteobacteria, irrespective of the presence or absence of TCE. Members of Gammaproteobacterial groups such as Pseudomonas, Bacillus, Stenotrophomonas and Acinetobacter sp are associated with TCE enrichment cultures or contaminated sites [45,46]. Alongside, alpha-and betaproteobacteria groups (also detected in this study), these organisms are believed to be involved in the co-metabolism of the TCE contaminant [46].…”
Section: Microbial Community Associated With Tce Dechlorinationmentioning
confidence: 86%
“…Aziz et al (2020) and Li et al (2015) reported that Variovorax sp. could biodegrade TCE with phenol being used as a carbon substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Total DNA was extracted from each sample by the bead beating technique (BioSpec, Shanghai, China) using the kit UltraClean DNA Isolation (Mo Bio Laboratories, BIOzym, Landgraaf, Netherlands). Polymerase chain reaction (PCR) amplification was implemented with bacterial primers 27F and 1492R ( Li et al, 2015 ), using a 25 μL reaction mixture containing the template 0.5 μL, each primer (10 mmol/L) 0.5 μL, TaqMix 12.5 μL, and ddH 2 O 11 μL. PCR was performed under the cycling conditions described as follows: initial denaturation at 94°C for 5 min, 25 cycles of denaturation at 94°C for 1 min, annealing at 50°C for 30 s, and extension at 72°C for 1 min, then re-extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%